2001
DOI: 10.1152/jappl.2001.90.3.865
|View full text |Cite
|
Sign up to set email alerts
|

In vivo specific tension of human skeletal muscle

Abstract: In this study, we estimated the specific tensions of soleus (Sol) and tibialis anterior (TA) muscles in six men. Joint moments were measured during maximum voluntary contraction (MVC) and during electrical stimulation. Moment arm lengths and muscle volumes were measured using magnetic resonance imaging, and pennation angles and fascicular lengths were measured using ultrasonography. Tendon and muscle forces were modeled. Two approaches were followed to estimate specific tension. First, muscle moments during el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
167
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(182 citation statements)
references
References 37 publications
11
167
4
Order By: Relevance
“…Numerous studies have examined how the PA affects normal muscle anatomy, architecture, and physiological function (Muhl, 1982;Gans and de Vree, 1987;Lieber and Blevins, 1989;Gans and Gaunt, 1992;Scott et al, 1993;Van Eijden et al, 1997;Ledoux et al, 2001;Maganaris et al, 2001). Previous PA studies have focused only on the PA of the muscle fibers located at the muscle belly surface (Muhl, 1982;Sacks and Roy, 1982;Lieber and Blevins, 1989;Scott et al, 1993;Van Eijden et al, 1997;Ledoux et al, 2001;Maganaris et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have examined how the PA affects normal muscle anatomy, architecture, and physiological function (Muhl, 1982;Gans and de Vree, 1987;Lieber and Blevins, 1989;Gans and Gaunt, 1992;Scott et al, 1993;Van Eijden et al, 1997;Ledoux et al, 2001;Maganaris et al, 2001). Previous PA studies have focused only on the PA of the muscle fibers located at the muscle belly surface (Muhl, 1982;Sacks and Roy, 1982;Lieber and Blevins, 1989;Scott et al, 1993;Van Eijden et al, 1997;Ledoux et al, 2001;Maganaris et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previous PA studies have focused only on the PA of the muscle fibers located at the muscle belly surface (Muhl, 1982;Sacks and Roy, 1982;Lieber and Blevins, 1989;Scott et al, 1993;Van Eijden et al, 1997;Ledoux et al, 2001;Maganaris et al, 2001). The orientation of these fibers; however, does not represent the orientation of the majority of muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 shows roll, pitch and yaw wrt time of a foot in extreme rotational movement. Previous measurements of ankle muscle strength have shown that the torque producing potential of the plantraflexors is smaller than 200Nm [21], [16]. For the dorsiflexors and the ankle invertors and evertors the maximum torque values produced during a strength test are smaller than 100Nm [16].…”
Section: Experimental Datamentioning
confidence: 85%